Diagnosa Penyakit pada Jamur Tiram Putih menggunakan Metode Dempster Shafer: ( Studi Kasus : Omah Jamur Tiram Stabat ) - Alfina Damayanti; Novriyenni Novriyenni; Rusmin Saragih (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
: Oyster mushrooms are one of the popular horticultural products in the community, with a significant increase in demand from year to year. However, farmers often face difficulties in identifying and preventing diseases that attack oyster mushroom plants, which have an impact on production stability. To overcome this problem, this study aims to design an expert system that can diagnose diseases in white oyster mushrooms using the Dempster Shafer Method. This system is designed to provide accurate diagnostic information and solutions to deal with diseases in oyster mushrooms, so as to improve the quality and quantity of production. This study also strengthens previous studies using the Certainty Factor method, with an emphasis on the use of expert knowledge to overcome disease problems in oyster mushroom cultivation. The case study was conducted at Omah Jamur Tiram Stabat, where the results of the implementation are expected to increase the effectiveness and efficiency of oyster mushroom cultivation in the area.